LEGAL BASIS OF PROTECTING CONSUMER RIGHTS IN THE TOURISM SERVICES SECTOR (European Journal of Interdisciplinary Research and Development, 2025)
The article examines the main aspects of the legal regulation of tourism services in the Republic of Uzbekistan, aimed at protecting consumer rights. It analyzes the main regulatory legal acts regulating the activities of tour operators and travel agents, including the Civil Code of the Republic of Uzbekistan, the Laws «On Tourism» and «On Protection of Consumer Rights». Particular attention is paid to typical violations of tourists' rights, such as false advertising, charging additional fees and violations in hotel services.